A validated modelling technique for incorporating residual stresses in glass structural design. (February 2021) - Achintha, Mithila
Abstract: This paper presents the development of a simple parabolic residual stress depth profile model for characterising residual stresses in construction-sector glass. The proposed model requires only the knowledge of the surface residual stress, which is usually available from glass manufacturers. Unlike the complex computational techniques reported in the literature, such as modelling physical, microstructural and mechanical phenomena of glass at different temperatures during manufacturing, the proposed model obviates the need for modelling multi-physics phenomenon of the generation of residual stresses. The proposed model also eliminates the need of sophisticated experimental equipment, such as Scattered-Light-Polariscopes (SCALP), which are usually not available among practicing engineers, in order to characterise the residual stresses. Residual stress predictions from the proposed parabolic model were validated against experimental results reported in the literature. Using the concept of eigenstrains, the paper also extends the results of the proposed parabolic residual stress depth profile model for incorporating the effects of residual stresses in stress analysis of glass structures.